Analysis of Students’ Critical Thinking Ability in Physics Learning at the High School Level - Risdha Reny Syarif; Usman Usman; A. Sri Astika Wahyuni; Trisno Setiawan (Universitas Lambung Mangkurat, 2025)
Analyzing the critical thinking ability of high school students in physics learning. The purpose of this survey study is to assess the critical thinking abilities of high school students studying physics in Jeneponto Regency during the 2024/2025 school year. The research sample consists of XII MIPA class students from three schools: SMAN 2 Jeneponto (32 students), SMAN 5 Jeneponto (28 students), and SMAN 11 Jeneponto (24 students). The analytical method employed was descriptive statistical analysis. The method of data collection utilized was a multiple-choice test on critical thinking ability. The instrument used is valid, and the reliability coefficient is 0,817. The indicators examined for critical thinking skills include providing simple explanations, developing basic skills, making inferences, and offering further explanations. According to the study's findings, the average score for students' critical thinking abilities in high school physics within the Jeneponto district is 6.48, with a percentage of 32%. 44%, falling into the low category, while the very high category comprises 30.95% with 26 students, the high category encompasses 40.47% with 34 students, the medium category includes 23.80% with 20 students, the low category represents 3.57% with three students, and the very low category denotes 1.19% with one student. The implications of this study are to enhance learning activities, for example, by utilizing innovative and interactive learning methods and evaluating students’ critical thinking skills.